Sixty years after ‘The mastodonts of Brazil’: The state of the art of South American proboscideans (Proboscidea, Gomphotheriidae) - Mothé, Dimila (2017)
Studies on South American Gomphotheriidae started around 210 years ago and, 150 years later, the classic study “The mastodonts of Brazil” by Simpson and Paula Couto (1957) attempted to clarify the complex issues related to our understanding of these proboscideans. Here, we update state of knowledge regarding proboscideans in South America subsequent to the publication of Simpson and Paula Couto (1957). The taxonomy of South American proboscideans is now stable and two species are recognized, Notiomastodon platensis and Cuvieronius hyodon. The former had a wide distribution in South America (from lowlands to highlands and from east to west coasts), while the latter was restricted to Ecuador, Peru and Bolivia. Although records of Notiomastodon are abundant and occur in almost overlapping geographic distribution with Cuvieronius, they have never been recorded in the same locality. Here, we evaluated over 500 South American localities with proboscidean remains, although only cranial and dental specimens show recognizable diagnostic features. As both proboscideans in South America had a generalist-opportunist alimentary strategy, a competitive exclusion probably precluded their sympatry. Their origin is most probably related to independent migrations from Central America during the Great American Biotic Interchange. They are not sister-taxa – Cuvieronius hyodon is sister-taxon of Rhynchotherium, and this clade is closer to Notiomastodon platensis than to the other proboscideans, supporting the hypothesis of independent origins. Notiomastodon platensis has a continuous record from the Early Pleistocene to Early Holocene, when it became extinct, probably due to synergy of human impact and climatic changes during the Pleistocene/Holocene transition. In contrast, extinction of Cuvieronius hyodon happened much earlier, and it was not related to the terminal Pleistocene event that lead the extinction of selected megafauna in South America, including Notiomastodon.